A tool for obtaining transparency and traceability in heterogeneous design automation environments. Issue 4 (4th July 2018) - Hjertberg, Tim; Stolt, Roland; Elgh, Fredrik
ABSTRACT: Today, CAD-system are used for much more than just geometric modeling. They are complemented by various software and information sources forming a complete environment for handling all life-cycle aspects of the product. In such systems, the CAD-system works as a central hub. The software and information sources may be of various types making the system highly heterogenous. This presents problems with transparency and traceability in the system making long term management difficult. In this paper, a novel tool is presented to keep track of the dependencies between the various parts of such systems providing an overview and making it possible to predict the effect of proposed changes and facilitating long term management. The tool is tested in a highly heterogeneous environment at a manufacturer of aerospace components, with the result that the traceability is expected to increase at the expense of that time must be spent on defining dependencies and meta-information as the system is evolving. GRAPHICAL ABSTRACT: